Slicepedia open corpus slicing for Adaptive Web Systems - Levacher, Killian (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2014)
The growing demand for user experiences on the web addressing individual needs, is driving the mainstream adoption of personalisation technologies across broad fields of interests. Adaptive Web Systems (AWSs) have traditionally attempted to deliver dynamically adapted and personalised experiences to users, through the sequencing and adaptation of recomposable content. The adaptivity offered by these systems however, can be restricted by a lack of sufficient resources, which represents a major obstacle to their widespread adoption. So as to serve the largest possible audience, common sense encouraged the labor intensive and limited production of such resources, to target the common and predictable needs of users in higher demand, by delivering one-size-fits-all recomposable material, of type and quantity predetermined in advance.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin